Pengaruh Lama Fermentasi Alami Terhadap Mutu Kopi Robusta Asal Bantaeng - Pratiwi, Putri; Yanto, Subari; Sukainah, Andi (Agricultural Technology Education Study Program, 2023)
Robusta coffee has a higher caffeine content than Arabica coffee. Coffee farmers in Bantaeng, South Sulawesi, do more post-harvest processing using the dry processing method or a natural process where the coffee that has been picked is immediately dried without removing the mucus first by fermentation, fermentation can reduce the content caffeine in coffee. Excessive caffeine in coffee can be harmful to health. The research aims to determine the effect of fermentation time on the quality of Robusta coffee beans and the decrease in caffeine levels. The research method used an experimental method with a completely randomized design (CRD) to determine the effect of natural fermentation time on the caffeine content of robusta coffee beans from Bantaeng district for 0.24, 48 and 72 hours. Data collection was carried out by testing the total microbes in the fermented liquid (total plate count, total bacteria, yeast count, and total lactic acid bacteria), pH, total titrated acid, water content, and caffeine content. The results of the analysis show that the duration of fermentation affects the decrease in caffeine content in Robusta coffee beans. The best treatment in this study was 48 hours of fermentation which had a caffeine content of 2.65%